If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(7 + -2a) = 4(-3a + 2) (7 * 2 + -2a * 2) = 4(-3a + 2) (14 + -4a) = 4(-3a + 2) Reorder the terms: 14 + -4a = 4(2 + -3a) 14 + -4a = (2 * 4 + -3a * 4) 14 + -4a = (8 + -12a) Solving 14 + -4a = 8 + -12a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '12a' to each side of the equation. 14 + -4a + 12a = 8 + -12a + 12a Combine like terms: -4a + 12a = 8a 14 + 8a = 8 + -12a + 12a Combine like terms: -12a + 12a = 0 14 + 8a = 8 + 0 14 + 8a = 8 Add '-14' to each side of the equation. 14 + -14 + 8a = 8 + -14 Combine like terms: 14 + -14 = 0 0 + 8a = 8 + -14 8a = 8 + -14 Combine like terms: 8 + -14 = -6 8a = -6 Divide each side by '8'. a = -0.75 Simplifying a = -0.75
| 8y-6y+2=3-10+y | | 4z+7= | | y=6x-4 | | 2=n/3-5 | | 2x+10=2x-0.8 | | x(2x-1)(x+4)=0 | | x(2x-1)(x+4)=8 | | 15y^2-17y-4=0 | | n/6+12=11 | | 7y+4(y-6)=4(y+2)-2 | | x-5x=7x-9-x | | 14=7-n | | 4x^2-28x=15 | | 5a+5a=40 | | x-2=-2x+3+3.5 | | 2(3)-2= | | -2(t-5)+9t=5t-3 | | 60x-41=-17 | | (x+4)+(x+2)+x=(x+2)+x-22 | | 3(2x+3)-3=6x+6 | | 2m-2=3 | | 3+6n=-63 | | y*2+3=2(y-2) | | 4x^2+48x+143=0 | | 6x+3=6(x+4) | | b*b+b=2 | | q-5=12 | | 4b-4=3b+2 | | 5x-3y=45 | | 180+3a=2a-25 | | 4a+6=26 | | 34=-5-9t |